First test for eradication of beavers (Castor canadensis) in Tierra del Fuego, Argentina - Jusim, Pablo; Goijman, Andrea Paula; Escobar, Julio; Carranza, María Luisa; Schiavini, Adrián (Springer, 2020)
The North American beaver (Castor canadensis) was introduced in 1946 from Canada to Isla Grande de Tierra del Fuego to develop a fur industry. Their expansion to most of the habitats of Tierra del Fuego and their presence on the continent, moved Argentina and Chile to test their eradication. The objective of this paper is to analyse a pilot eradication test and determine which variables are associated with the capture success of beavers in a small area of the Fuegian forest. The pilot was conducted in the Corazón de la Isla reserve, Tierra del Fuego, Argentina, during April and May 2014, by three groups of trappers, using body-grip traps and snares. The capture success was modelled with different variables. A total of 115 individuals were captured after 590 and 265 body-grip and snare trapping-nights, respectively, with an overall efficiency of 13.5%. Using body-grip traps and placing traps in slides or burrows would increase trapping efficiency. This experience allowed us to evaluate techniques and generate recommendations for future beaver eradication trials on a larger scale: (a) the need to improve the data collection system through digital technology and georeferencing the location of operations, (b) the importance of the type of trap used according to the specific sites of the colony, (c) test alternative trapping strategies to reduce the eventual “learning” of animals, (d) drive the paradigm of hunters from yield oriented to eradication objectives and (e) ensure the political sustainability of the wider program.